Psychological first aid for minors after Hurricane Otis in Acapulco, Mexico (Revista Estudios Psicológicos, 2024)
Hurricane Otis, a category five storm, struck the cities of Acapulco and Coyuca de Benítez (Guerrero) on October 25, 2023, at 12:25 a.m. This phenomenon devastated a large part of the infrastructure in the affected cities, impacting the Acapulco and Coyuca populations in terms of both material and personal losses. The objective of this study is to understand the experiences of children and adolescents in Acapulco, with the aim of providing them with appropriate emotional management strategies that facilitate the activation of their coping mechanisms, minimize future psychological harm, and, if necessary, refer them to specialized institutions. The ultimate goal of this program is to contribute to community health and well-being. A qualitative research approach was employed, utilizing a hermeneutic phenomenological design and thematic category analysis. The sample consisted of 34 minors. The instruments used included participant observation and field journals, while the techniques applied encompassed narrative expression, free expressive drawing, and children's storytelling. The results indicated that the children developed adaptive functions to cope with the situation. Those who exhibited psychosocial and mental health issues were referred to specialized institutions. Psychological support was found to mitigate the psycho-emotional impact of the experience. It is recommended that more spaces be created for minors to express the challenges they face and that the development of their socio-emotional skills be encouraged.
Keywords: community resilience; emergencies; human security; natural disaster; psychological effects